Parents' right strategy on preventing youngsters' recent suicidal ideation: a 13-year prospective cohort study. (4th May 2022) - Chiang, Yi-Chen; Lin, Yu-Jung; Li, Xian; Lee, Chun-Yang; Zhang, Shuoxun; Lee, Tony Szu-Hsien; Chang, Hsing-Yi; Wu, Chi-Chen; Yang, Hao-Jan
Abstract: Background: Suicide remains the second leading cause of death among youths. Family-related factors are considered important determinants of children's suicidal ideation, whereas their short-/long-term influence is seldom quantified. Aims: We aim to confirm the simultaneous/lagged effects of family-related factors on the occurrence of recent suicidal ideation from childhood to young adulthood (aged from 10 to 22 years old). Method: Data were derived from a longitudinal prospective cohort study. Participants included 2065 students who were followed up for 13 years. Generalized estimating equations were used to clarify the influential effects of family-related factors on suicidal ideation during the past month. Results: The peak of the rate of recent suicidal ideation arrived during junior high school years. Family interaction, family support, family involvement, and parental punishment had simultaneous effects on recent suicidal ideation. Family involvement, parental conflict, and psychological control had lagged and lasting effects on suicidal ideation. Notably, the lasting protective effects of family involvement were more obvious than simultaneous effects. Conclusions: Providing parents with sustained support and education to improve their "positive parenting literacy" can help with their children's mental health development. This is especially the case during COVID-19 quarantine periods when families spend the most time together at home.